Simultaneous selection for yield and stability of Chickpea (Cicer arietinum) germplasm through AMMI based parameters - PATHY, T LAKSHMI; REDDY, A TRIVIKRAMA; GOWDA, JAYARAME; JAYALAKSHMI, V; VIJAYABHARATHI, A (The Indian Journal of Agricultural Sciences, 2022)
Identifying a stable variety is essential before recommending it for cultivation at a particular location. In the present study, 23 chickpea (Cicer arietinum L.) genotypes were evaluated for pod yield per plot in randomized complete block design at Hebbal, Gouribidanur, and Nandyal during 2015–17. Among the three environments, Nandyal had the highest environmental index with a high mean yield. Pooled analysis of variance indicated significant differences due to environment, genotypes, and their interaction, necessitating the selection of genotypes with general and specific adaptation. AMMI (Additive main effects and multiplicative interaction) analysis extracted two significant principal components which explained all the variation. Univariate parametric measures like Francis’ coefficient of variation, Wricke’s ecovalence, Lin and Binns’ superiority index, Eberhart and Russel’s regression coefficient (bi), and deviation from linearity (S2di) were estimated along with AMMI based parameters, which include either one or both significant principal components. Most of these measures had similar rankings for genotypes. Rank sums were calculated for genotypes over these stability parameters, where DCP-92-3, BG-212, and KAK-2 had the best ranks. Simultaneous selection indices were constructed assigning equal weightage to yield and stability for each of the AMMI-based parameters, and the genotypes DCP-92-3, BG-212, and KAK-2 had the highest index values. All the analyses were performed in R studio. Based on the above measures, it can be concluded that these three genotypes are stable and can be cultivated to obtain stable yields across environments.